Listening Comprehension Hindrances of EFL (English Foreign Language) Learners on 2016/2017 in English Study Program of Universitas Islam Riau - Hadijah, Sitti; Shalawati, Shalawati (J-SHMIC : Journal of English for Academic, 2017)
As one of essential skills to master a language, listening subject is provided as one of compulsory subjects to the learners in English study program at university level in order to help them in improving their English skill in term of having good ability in comprehending spoken information delivered by native or non-native speakers of English in various contexts of communication.Despite of having long term English learning experiences and easy access of learning sources, the learners seem still having hindrances in listening comprehension skill. Based on researcher’s experiences in teaching interpretative listening subject to the first year students of English study program, most of the students did not actively involve during the teaching and learning activities, they also had low performances on listening.In relation to the phenomena, this study was conducted with a descriptive research design in order to answer a question about the first year students’ listening comprehension hindrances. The participants were 30 students undertaking interpretative listening subject on 2016/2017 academic year at English Study Program, Universitas Islam Riau. Distributing questionnaire and interviewing the learners were done in collecting the data. Then, the findings show that there are five factors encountered by the learners as their hindrances in listening activities; inadequate listening practices, speed-rate of speakers, pronunciation, unknown vocabulary, and grammatical understanding